Maturation of type I and type II rat vestibular hair cells in vivo and in vitro - Borrajo, Mireia; Sedano, David; Palou, Aïda; Giménez-Esbrí, Víctor; Barrallo-Gimeno, Alejandro; Llorens, Jordi (Frontiers in Cell and Developmental Biology, 2024)
Vestibular sensory epithelia contain type I and type II sensory hair cells (HCI and HCII). Recent studies have revealed molecular markers for the identification of these cells, but the precise composition of each vestibular epithelium (saccule, utricle, lateral crista, anterior crista, posterior crista) and their postnatal maturation have not been described in detail. Moreover, in vitro methods to study this maturation are not well developed. We obtained total HCI and HCII counts in adult rats and studied the maturation of the epithelia from birth (P0) to postnatal day 28 (P28). Adult vestibular epithelia hair cells were found to comprise ~65% HCI expressing osteopontin and PMCA2, ~30% HCII expressing calretinin, and ~4% HCII expressing SOX2 but neither osteopontin nor calretinin. At birth, immature HCs express both osteopontin and calretinin. P28 epithelia showed an almost adult-like composition but still contained 1.3% of immature HCs. In addition, we obtained freefloating 3D cultures of the epithelia at P1, which formed a fluid-filled cyst, and studied their survival and maturation in vitro up to day 28 (28 DIV). These cultures showed good HC resiliency and maturation. Using an enriched medium for the initial 4 days, a HCI/calretinin+-HCII ratio close to the in vivo ratio was obtained. These cultures are suitable to study HC maturation and mature HCs in pharmacological, toxicological and molecular research.